\[\boxed{\text{445\ (445).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ 4a + 4 = 4 \cdot (a + 1).\]
\[2)\ 6ab - 3b = 3b \cdot (2a - 1).\]
\[3) - 5x - 10y = - 5 \cdot (x + 2y).\]
\[4)\ x^{6} - x^{4} + x^{2} =\]
\[= x^{2} \cdot \left( x^{4} - x^{2} + x \right)\text{.\ }\]
\[\boxed{\text{445.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ \overline{\text{ab}} + \overline{\text{bc}} + \overline{\text{ca}} =\]
\[= 10a + b + 10b + c + 10c + a =\]
\[= 11a + 11b + 11c =\]
\[= 11 \cdot (a + b + c) - делится\ \]
\[на\ 11.\]
\[Что\ и\ требовалось\ доказать.\]
\[= 99 \cdot (a - c) - делится\ на\ 99.\ \]
\[Что\ и\ требовалось\ доказать.\]